RURAL LIFE, SOCIOECONOMIC STATUS AND DYNAMICS OF LIVELIHOOD: A CASE STUDY OF AN AGRARIAN VILLAGE IN ASSAM - Heena Khan, Silpi Sikha Hazarika (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The rural life surrounds around agriculture, farming and people with different cultural backgrounds. The river is been continuously changing the landscape of the areas nearby. Naltali is a village which has been going on transformation in terms of livelihood. The village has been changing due to some external forces both political and social leading in the change of the land use pattern and agricultural dynamics. The paper is therefore an attempt to investigate the present socioeconomic status and changing nature of rural life and livelihood in village, called Naltali in Naga on district of Assam. The village is inhabited by indigenous non-tribal Assamese people. The village is surveyed through interaction with the local people and focus group discussion has been conducted. A household survey covering the entire families of the village was conducted with a purposively designed schedule to generate first hand data and information for the purpose.